IoT-based Smart Pond Controller to Optimize Freshwater Fish Production and Data Management Application to Improve the Quality of Administration of Freshwater Fish Farmers in Pagelaran, Pringsewu Regency Lampung - Alita, Debby; Surahman, Ade; Sarida, Munti (STKIP Singkawang, 2024)
The main problems that are a priority to be resolved are: 1) Systems that are still manual; 2) Often experience large losses due to poor water quality (high water pH); 3) Records of fish feed processing and financial management which are still done manually. Based on the priority problems faced by partners, the solutions offered by the proposing team for this PKM scheme are: 1) Implementing an IoT-based Smart Pond: Water Quality Control Tool, Automatic Feeding, IoT-Based Predator Detection; 2) Implementing Smart Pond: Web-based cultivation data management application; 3) Providing educational training on freshwater fish cultivation for breeders and all EWAK POND employees. The result of this service is that by implementing IoT technology, automatic feeding can reduce the amount of daily feed so that it can save farmers' expenses, reduce mortality rates, and improve fish farming management. Apart from that, this program also aims to empower local breeders through training and mentoring, so that they can better understand and utilize this technology for the sustainability of their businesses